Victims of the Pandemic? European Far-Right Parties and COVID-19 - Wondreys, Jakub (Natl Pap, 2020)
It has become received wisdom that the pandemic has “exposed” the political incompetence of far-right parties in government and that far-right parties in opposition have become its (first) “victims.” This is largely based on the generalization of one or two individual cases—most notably US president Donald Trump—who is the exception rather than the rule. This article provides a comparative analysis of far-right responses to the COVID-19 pandemic within the European Union. Based on theoretical insights from previous research, we expect the responses to reflect the main ideology and the internal heterogeneity of the contemporary far right as well as to show the increasing mainstreaming of its positions. We analyze four different, but related, aspects: (1) the narratives about COVID-19 from far-right parties; (2) the proposed solutions of far-right parties; (3) the electoral consequences of the pandemic for far-right parties; and (4) the success of far-right parties in dealing with the pandemic. Finally, in the discussion we shortly look ahead at the possible consequences of a highly likely second outbreak of COVID-19.